Just and Righteous Causes : Rabbi Ira Sanders and the Fight for Racial and Social Justice in Arkansas, 1926-1963 - Moses, James L., 1960- (Book collections on Project MUSE., 2018)
"Little Rock Rabbi Ira Sanders was a dynamic force for social justice and racial equality in Arkansas. His lifetime devotion and many activities on behalf of bold social activism provide a means to analyze not only his specific contributions to Arkansas history, but also the larger story of the movements for racial and social justice in Arkansas and the twentieth-century south. This is the first biography written about this influential figure in Little Rock history"--